Fatigue leads to altered spinal kinematics during high performance ergometer rowing - Urbanczyk, C. A.; Miller, E.; McGregor, A. H.; Bull, A. M. J. (ISBS Proceedings Archive (Michigan), 2020)
Low back injuries in rowing are attributed to intense, repetitive, loading through the spine. Good technique and postural control are essential to maximize performance and minimize injury risk. This motion capture study recorded 3D spinal kinematics of 14 athletes during rowing at varying speeds on an instrumented ergometer and correlated motion with power metrics and athlete demographics. Sagittal plane rotation decreases in the lumbar spine and increases in the thoracic spine as speed increases. Transverse and frontal planes have little influence on force output. Declining postural control can be seen within each trial and worsened with higher rate. Assessments of form differences across athletes using relative motion between spine segments at critical stroke points show greater lumbar flexion (compared to thoracic) at the catch and neutral alignment at max handle force.